Myelin-associated glycoprotein gene mutation causes Pelizaeus-Merzbacher disease-like disorder. (15th July 2015) - Lossos, Alexander; Elazar, Nimrod; Lerer, Israela; Schueler-Furman, Ora; Fellig, Yakov; Glick, Benjamin; Zimmerman, Bat-El; Azulay, Haim; Dotan, Shlomo; Goldberg, Sharon; Gomori, John M.; Ponger, Penina; et al.
Abstract : Pelizaeus-Merzbacher disease is an X-linked hypomyelinating leukodystrophy. Lossos et al. describe a family with an early-onset Pelizaeus-Merzbacher disease-like phenotype that slowly evolves into complicated hereditary spastic paraplegia, affecting both the CNS and PNS. Exome sequencing reveals a causative homozygous missense mutation in MAG, which encodes myelin associated glycoprotein. Abstract : Abstract : Pelizaeus-Merzbacher disease is an X-linked hypomyelinating leukodystrophy caused by mutations or rearrangements in PLP1 . It presents in infancy with nystagmus, jerky head movements, hypotonia and developmental delay evolving into spastic tetraplegia with optic atrophy and variable movement disorders. A clinically similar phenotype caused by recessive mutations in GJC2 is known as Pelizaeus-Merzbacher-like disease. Both genes encode proteins associated with myelin. We describe three siblings of a consanguineous family manifesting the typical infantile-onset Pelizaeus-Merzbacher disease-like phenotype slowly evolving into a form of complicated hereditary spastic paraplegia with mental retardation, dysarthria, optic atrophy and peripheral neuropathy in adulthood. Magnetic resonance imaging and spectroscopy were consistent with a demyelinating leukodystrophy. Using genetic linkage and exome sequencing, we identified a homozygous missense c.399C>G; p.S133R mutation in MAG. This gene, previously associated with hereditary spastic paraplegia, encodes myelin-associated glycoprotein, which is involved in myelin maintenance and glia-axon interaction. This mutation is predicted to destabilize the protein and affect its tertiary structure. Examination of the sural nerve biopsy sample obtained in childhood in the oldest sibling revealed complete absence of myelin-associated glycoprotein accompanied by ill-formed onion-bulb structures and a relatively thin myelin sheath of the affected axons. Immunofluorescence, cell surface labelling, biochemical analysis and mass spectrometry-based proteomics studies in a variety of cell types demonstrated a devastating effect of the mutation on post-translational processing, steady state expression and subcellular localization of myelin-associated glycoprotein. In contrast to the wild-type protein, the p.S133R mutant was retained in the endoplasmic reticulum and was subjected to endoplasmic reticulum-associated protein degradation by the proteasome. Our findings identify involvement of myelin-associated glycoprotein in this family with a disorder affecting the central and peripheral nervous system, and suggest that loss of the protein function is responsible for the unique clinical phenotype.